Acceptance of Islamic banking as innovation: a case of Pakistan. Issue 4 (13th November 2017) - Ali, Muhammad; Puah, Chin-Hong
Abstract : Purpose: This study aims to investigate the factors that determine the customer adoption of Islamic banking in Pakistan. Design/methodology/approach: This paper aims to use a sample of 540 Islamic bank customers located in the biggest city of Pakistan (Karachi). This study is based on the diffusion of innovation (DOI) theory and analyzed the role of five attributes (compatibility, relative advantage, complexity, observability and trialability) along with the consumer awareness about the customer adoption of Islamic banking. Additionally, the present research also considers Islamic banking as a new idea (innovation) in Pakistan under the framework of DOI theoretical assumptions. The exploratory and confirmatory factor analyses are applied to the sample data. The theoretical framework is then tested using structural equation modeling. Findings: The findings of the study revealed that all five attributes of the DOI theory are positively and significantly related to the customer adoption of Islamic banking. The customer awareness also proved its importance in the hypothesized model by representing a positive and significant relationship. Originality/value: The present study provides a useful guideline for the Islamic bank managers and the academicians to better understand the customer adoption of Islamic banking.